Sharing Knowledge and Value for Nurturing Socioecological Production Landscapes: A Case of Payment for Ecosystem Services in Rejoso Watershed, Indonesia - Leimona, B.; McGrath, F.L.; Khasanah, N. (Springer, 2020)
Socioecological production landscapes (SEPLS) are multifunctional and substantially contribute to biodiversity conservation and ecosystem service provisions. Payment for ecosystem services (PES) is a policy tool that incentivizes landholders in production landscapes through voluntary and performance-based conservation contracts towards creating SEPLS that benefit all societies living within landscape. The design of PES covers explicitly defining ecological baselines of targeted landscape, calculating conservation opportunity costs, customizing contract agreement and payment modalities, and targeting agents with credible land claims and threats to ecosystem service degradation. Reverse auction represents a method to efficiently allocate contracts for the provision of ecosystem services in PES schemes. The PES gains allocative efficiency as contracts are allocated to the lowest-cost providers of ecosystem services through competitive bidding. In the context of developing countries, conservation contracts of PES scheme are mostly assigned to farming groups. Thus, a group-level auction was organized to accommodate collective decision-making in payment level for the scheme. This chapter is to discuss how group-level auctions enhance allocative efficiency due to sharing process during the auctions compared to the individual-level auction. A group auction allows exchanging and sharing knowledge, information and conservation values among farmer group members. The analysis shows that by allowing the group members to communicate with each other, sharing knowledge and value happened. This knowledge and value sharing encompasses how they understand the competitive bidding process, how their bids can influence the overall outcomes of winning or losing the conservation contracts, and the most importantly, how farmers share their conservation values as agricultural conservation efforts of PES not only benefit the external actors but also co-benefits themselves. This chapter presents the results from a PES pilot in Rejoso watershed, Indonesia, where smallholders in the up- and midstream are contributing to better watershed services, i.e. water infiltration and sedimentation reduction, to benefit downstream domestic and industrial water users.